Characteristics of Driver Perception of Road Elements and Road Conditions (Eurasian Journal of Engineering and Technology, 2023)
Measures taken in the field of road safety of the Republic of Uzbekistan, instructions and legal documents of our President Shavkat Mirziyoyev show that road safety is the most important problem of our time. On February 11, 2022, under the chairmanship of the President of the Republic of Uzbekistan, Shavkat Mirziyoev, a video selector meeting was held on measures to ensure human safety on the roads. The leader of our country emphasized that this issue has not been seriously and analytically discussed by any leader or organization in the last five years, the laws and works in this field are completely unsatisfactory, the issue of road safety has gone out of the way, and this is the reason for many people's objections